Biogeochemistry : an analysis of global change - Schlesinger, William H. (Academic Press, an imprint of Elsevier, 2013)
For the past 4 billion years, the chemistry of the Earth's surface, where all life exists, has changed remarkably. Historically, these changes have occurred slowly enough to allow life to adapt and evolve. In more recent times, the chemistry of the Earth is being altered at a staggering rate, fueled by industrialization and an ever-growing human population. Human activities, from the rapid consumption of resources to the destruction of the rain forests and the expansion of smog-covered cities, are all leading to rapid changes in the basic chemistry of the Earth. This book considers the effects of life on the Earth's chemistry on a global level. This text employs current technology to help students extrapolate small-scale examples to the global level, and also discusses the instrumentation being used by NASA and its role in studies of global change. With the Earth's changing chemistry as the focus, this text pulls together the many disparate fields that are encompassed by the broad reach of biogeochemistry.